On the Nature of Pre-Literate Spelling Ability - O'Grady, William D.; Gibbons, Diana E. (Kansas Working Papers in Linguistics, 1981)
In this paper, we examine the nature of spelling ability in adults, relating this type of representational competence to aspects of phonological and cognitive development as well as to schooling. The phenomenon of pre-literate spelling in young children is assessed in light of what can be inferred about spelling ability in adults.